Regionalization and federalization in European Union: Application of the principle of subsidiarity - Christian Ene-Corbeanu (Budgetary Research Review (BRR), 2010)
Regionalization and Federalization in European Union are concepts which should be clarified in order to assure best financial allotments through EU budget. Historical background can direct EU policies giving good practice guidelines for the future. Starting from the European models, now when all kinds of approaches began to be made with the intention to compromise the idea of local and regional autonomy, subsidiarity should be applied across EU.
Keywords: H77; N94; 330; federalization; regions